Promoting Hospitality and Tourism through Library and Information Services in the 21st Century - Adeniji, Paulina Olufunke (Journal of Service Science and Management., 2020)
This paper focused on the promotion of hospitality and tourism activities through the provision of library services. Information is a valuable resource for enterprises and people alike because they rely on correct information to perform daily activities. Libraries act as gateway or access point to information, concepts, and works of creativity. Services in libraries and information centres play an important role in the advancement of hospitality and tourism businesses. The paper focuses on essential library and information services to promote hospitality and tourism businesses. These library and information services include: making available resources such as maps, directories, bibliographies, biographies, referral services to mention but few. The services highlighted are aimed to promote hospitality and tourism activities in the 21st century.
Keywords: Hospitality; Tourism; Libraries; Information Service; Information Use